2012
DOI: 10.1177/0300985812447826
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis in Bovine Viral Diarrhea Virus (BVDV)–Induced Mucosal Disease Lesions

Abstract: Cattle persistently infected with a noncytopathic Bovine viral diarrhea virus (BVDV) are at risk of developing fatal “mucosal disease” (MD). The authors investigated the role of various apoptosis pathways in the pathogenesis of lesions in animals suffering from MD. Therefore, they compared the expression of caspase-3, caspase-8, caspase-9, and Bcl-2L1 (Bcl-x) in tissues of 6 BVDV-free control animals, 7 persistently infected (PI) animals that showed no signs of MD (non-MD PI animals), and 11 animals with MD an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 44 publications
0
6
1
Order By: Relevance
“…The PI3K/Akt pathway plays an anti-apoptotic role through inhibiting the caspase 9 signaling cascade (37). In BVDV infected cattle, the expression of caspase 9 and caspase 3 is involved in lymphoid tissues lesions, but whether it directly induces apoptosis in infected cells or whether it is related to the PD-1 pathway remains unclear (38). In our study, by measuring the levels of p-PI3K, p-Akt, p-mTOR, p-ERK, cleaved-caspase 9, and cleaved-caspase 3, we confirmed that CP BVDV infection can inhibit the proliferation of CD4 + and CD8 + T cells and induce apoptosis via PD-1-mediated repression of PI3K/Akt/mTOR and ERK pathways and activation of the caspase 9/caspase 3 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The PI3K/Akt pathway plays an anti-apoptotic role through inhibiting the caspase 9 signaling cascade (37). In BVDV infected cattle, the expression of caspase 9 and caspase 3 is involved in lymphoid tissues lesions, but whether it directly induces apoptosis in infected cells or whether it is related to the PD-1 pathway remains unclear (38). In our study, by measuring the levels of p-PI3K, p-Akt, p-mTOR, p-ERK, cleaved-caspase 9, and cleaved-caspase 3, we confirmed that CP BVDV infection can inhibit the proliferation of CD4 + and CD8 + T cells and induce apoptosis via PD-1-mediated repression of PI3K/Akt/mTOR and ERK pathways and activation of the caspase 9/caspase 3 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…To confirm the presence of antigen, immunohistochemical staining used in this study provided a highly specific and sensitive method to assess the presence of BDV in placental tissue and fetal organs such as thyroid gland, tongue, and skin. 7,9,20,22,41 All uteri, placentas, and fetuses were macroscopically normal, and no histologic abnormalities were found in the fetal organs. There was histological evidence of inflammation in the placentomes of the 3 heifers in which virus could be identified by immunohistochemical staining, which differs from the placentitis observed in sheep infected with noncytopathic BDV, in BVDV-infected ewes, 29,35,39 and also in BVDV-PI fetuses of pregnant cows, in which placentitis is absent.…”
Section: Discussionmentioning
confidence: 95%
“…A role for the adaptive intrinsic apoptosis pathway has been reported in persistent pestiviral infections, as described for mucosal disease–associated lesions . 20 During normal pregnancy, this pathway is also known to be activated, as the number of apoptotic cells increases significantly in the maternal crypt epithelium, maternal stroma, and fetal chorionic epithelium. 5 We were unable to detect any enhanced activation of the pathway in infected animals compared to controls, suggesting it is unlikely to be significantly involved.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations